Evaluating the Contribution of Civil Society Organizations in Raising Awareness and Building Confidence in the Institutions of the State Within the Framework of the National Strategy Anti-Corruption 2014-2018 - Oweis, Rawia (The Arab Journal of Administration, 2018)
The objective of the research is to focus on the contribution of civil society organizations since the launching of the National Strategy 2014-2018 to fight corruption, especially in organizing and disseminating information, raising public awareness and building trust in governmental institutions and cooperating with the regulatory, executive and judicial bodies in combating various corruption crimes. The issue of struggling corruption is a common responsibility and interest of all the actors in the same society. It involves all stakeholders› individuals, governmental institutions, media, and civil society organizations such as trade unions, parties, economic, social and cultural associations. The descriptive and descriptive approach was used in the research to extract and induce the explanatory results and the different relations between independent and intermediate variables related to research using the survey model to collect data for a sample unit of different citizens to test the hypotheses of the executive and supervisory roles of the civil society to reduce the phenomenon of corruption according to the national strategy. The results of the analytical study showed that both the executive role and the supervisory role-play an important moral role in influencing the public awareness. However, the executive role contributes to the weakness of the supervisory role, especially under the current legislation to combat corruption, which makes the supervisory role essential for the sovereign bodies. Civil society is mostly the executive activities carried out voluntarily and selectively. The role of civil society organizations in building trust differs from their role in spreading public awareness in a different form. The supervisory role is clearly more influential than the executive role. The current legislation gives a degree of legal control over civil society organizations› performance. The supervisory performance of the state institutions and hence the building of trust in what is limited due to the nature of the institutions as sovereign bodies enjoy independence and confidentiality of its work.